Claudia Jones: : A Life in Exile - Sherwood, Marika (Book collections on Project MUSE., 2015)
Every year over a million people pack the streets of London's Notting Hill for Carnival, but as the carnival-goers soak up the sights, sounds and smells of the festival, few appreciate that its founder died in poverty on Christmas Eve in the bitterly cold winter of 1964, the end of a life dogged by struggle and illness. Claudia Jones: A Life in Exile is the first book to chart the life and work this visionary and pioneer. Born in Trinidad in 1915, Claudia Jone's family moved to Harlem, New York, where the young Claudia became a leading figure in Communist and black politics. Forced into exile in Britain in 1955, Jones arrived in London penniless and friendless. She became active in civil rights campaigns amongst the new West Indian communities established in the capital and launched an annual Carnival to showcase the talents and culture of the Afro-Caribbean community. The book's particular focus is on the time that Jones spent in Britain Claudia Jones: A Life in Exile is a fitting and long overdue testament to a remarkable woman who was quite simply years ahead of her time.